Materialy k obosnovaniju predloženij po soveršenstvovaniju EVSK. Cast' II. Normativno-pravovye, metodologiceskie i organizacionnye aspekty sovremennoj Edinoj vserossijskoj sportivnoj klassifikacii - Kubeev, A. V.; Mochalova, M. S.; Savenkova, E. A.; Evtoukh, A. V.; Chaykovskaya, O. O.; Vorobyov, V. S. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
The proposed study continues a series of articles on the justification of proposals for improving the Unified All-Russian Sports Classification (UARSC). The article, which follows the line of the previous work (Part I), defines the need to improve the UARSC. It presents the results of discussion and analysis of the fundamental documents and materials of the UARSC. The prerequisites are identified for the transition to the improvement of the UARSC as a holistic information system, in the context of the development and creation of digital technologies, with the aim of facilitating more flexible and efficient information support for sports in the country.